Woman as the Embodiment of Desire in Algirdas Landsbergis’ Short Stories - Bankauskaitė, Gabija; Vaišvylaitė, Domantė (Respectus Philologicus, 2023)
The woman as the embodiment of desire in the writings of Algirdas Jeronimas Landsbergis (1924–2004) – a Lithuanian expatriate playwright, novelist, editor, and literary and theatre critic – is not an ordinary literary character but symbolises the unique relationship between the rational world of consciousness and the instinctive, primal needs expressed in creative fantasies. The image of the woman-fantasy appears in the author’s short stories. It allows us to explore the inherent egocentricity of desire, the experience of lust that constrains subjectivity. C. G. Jung’s philosophy is used to classify fantasy images and identify their characteristic features, while E. Husserl’s phenomenology of consciousness is applied to the description of the protagonists’ experiences in the process of unique emotional occurrences. Short stories “Duet for Female Voice and Violin in Venice”, “A Long Night”, and “The Second Mountain Range” are analysed as expressions of the experiencing consciousness and the creating unconscious. The desires and fantasies of the protagonists materialise into a woman who is seen as a creation of lust; her body is reified by demonstrating power. However, a phantasmatic metamorphosis of characters is powerless to solve their dilemmas and inner confusion, as lust is based on one-sided, searching, and striving relations with the world in the absence of any answer.